ASPECTS OF THE TREATMENT OF CHRONIC HEART FAILURE - Khairillayeva Mehriban Khurshedovna; Vafoeva Nigora Abrorovna (Journals Park Publishing, 2024)
For several decades, chronic heart failure (CHF) has remained one of the most pressing problems in the developed countries of the world. Despite the great successes and achievements of medicine in the treatment of cardiovascular diseases, the prevalence of CHF is steadily increasing, ranging from 1.5 to 2.0% in the general population, and among people over 65 years of age it reaches 6-17%. CHF is characterized by a high level of disability and mortality of the population. More than 70% of men and 63% of women with CHF die within 6 years after the first clinical manifestations of the disease. According to some researchers, CHF will become the main problem of cardiology that society will have to face in the next 50 years [1, 7].